Power Systems, 3rd Edition - Grigsby, Leonard L. (CRC Press, 2017)
Power Systems, Third Edition (part of the five-volume set, The Electric Power Engineering Handbook) covers all aspects of power system protection, dynamics, stability, operation, and control. Under the editorial guidance of L.L. Grigsby, a respected and accomplished authority in power engineering, and section editors Andrew Hanson, Pritindra Chowdhuri, Gerry Sheblé, and Mark Nelms, this carefully crafted reference includes substantial new and revised contributions from worldwide leaders in the field. This content provides convenient access to overviews and detailed information on a diverse array of topics. Concepts covered include: Power system analysis and simulation Power system transients Power system planning (reliability) Power electronics Updates to nearly every chapter keep this book at the forefront of developments in modern power systems, reflecting international standards, practices, and technologies. New sections present developments in small-signal stability and power system oscillations, as well as power system stability controls and dynamic modeling of power systems. With five new and 10 fully revised chapters, the book supplies a high level of detail and, more importantly, a tutorial style of writing and use of photographs and graphics to help the reader understand the material. New chapters cover: Symmetrical Components for Power System Analysis Transient Recovery Voltage Engineering Principles of Electricity Pricing Business Essentials Power Electronics for Renewable Energy A volume in the Electric Power Engineering Handbook, Third Edition Other volumes in the set: K12642 Electric Power Generation, Transmission, and Distribution, Third Edition (ISBN: 9781439856284) K13917 Power System Stability and Control, Third Edition (9781439883204) K12650 Electric Power Substations Engineering, Third Edition (9781439856383) K12643 Electric Power Transformer Engineering, Third Edition (9781439856291).